Role of omega-3 polyunsaturated fatty acids in diet of patients with rheumatic diseases - P. Spinella; F. Oliviero; C. Sales (PAGEPress Publications, 2011)
The beneficial effects of ω-3 polyunsaturated fatty acids have been widely described in the literature in particular those on cardiovascular system. In the last decade there has been an increased interest in the role of these nutrients in the reduction of articular inflammation as well as in the improvement of clinical symptoms in subjects affected by rheumatic diseases, in particular rheumatoid arthritis (RA). Nutritional supplementation with ω-3 may represent an additional therapy to the traditional pharmacological treatment due to the anti-inflammatory properties which characterize this class of lipids: production of alternative eicosanoids, reduction of inflammatory cytochines, reduction of T-lymphocytes activation, reduction of catabolic enzymes activity. The encouraging results of dietetic therapy based on ω- 3 in RA are leading researchers to test their effectiveness on patients with other rheumatic conditions such as systemic lupus erythematosus and ankylosing spondylitis. Nutritional therapy based on food rich in ω-3 or on supplementation with fish oil capsules, proved to be a valid support to he treatment of chronic inflammatory rheumatic diseases.